Investigation on the properties of new palm-oil-based polyurethane modified bitumen - Kok, Baha Vural; Aydogmus, Ercan; Yilmaz, Mehmet; Akpolat, Mustafa (Elsevier Sci Ltd, 2021)
Polyurethane-derived polymer synthesized by the reaction of 4.4'-diphenylmethane diisocyanate (MDI) with the new modified palm-oil-based polyol was used as an alternative additive to thermoplasticelastomers, such as styrene-butadienestyrene (SBS), the most commonly used additive. The study aimed to investigate the effect of polyurethane (PU) modification on the rheological and chemical structure of base bitumen. The softening point, rotational viscosity, dynamic shear rheometer (DSR), multi-stress creep recovery (MSCR), bending beam rheometer (BBR), and Fourier transform infrared (FTIR) tests were conducted on the binders. The effects of curing time and temperature, isocyanate/hydroxyl (NCO/OH) molar ratio, and PU content were examined and the best modification conditions were determined. It was found that 24 h curing conditions at 85 degrees C were sufficient for the formation of PU bonds and these processes increased the rutting parameter of the binder by 256% compared to 1 h curing. At 50 degrees C and a frequency of 5 Hz, the binder with a 4:1 NCO/OH ratio had 63% more complex modulus than the binder with a 10:1 NCO/OH ratio. The 7 wt% PU modified binder had the same performance level as 4% SBS modification and 10 wt% PU modified binder was one degree higher. Moreover, above 60 degrees C, all the PU modified binders gave lower phase angles compared to the 4% SBS modified binder. 7 wt% PU modified binder showed similar elastic properties against cracks at low temperatures compared to the 4% SBS modified binder. The use of palm oil in the synthesis of PU presents an environmentally friendly and cost-effective solution compared to the use of petrochemical derivatives. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Bitumen; Modified palm oil; Polyurethane; Rheology; Material processing